2015
DOI: 10.1890/14-0106.1
|View full text |Cite
|
Sign up to set email alerts
|

The influence of birth date via body mass on individual fitness in a long‐lived mammal

Abstract: The timing of birth has marked impacts on early life and early development of newborns in many species. In seasonal environments, early-born offspring often survive and grow better than late-born offspring, but despite the long-lasting effects of early conditions on life history traits, the influence of birth date on fitness has rarely been investigated for longlived species. In this study, we analyzed both the short-and long-term effects of birth date on individual life history traits and explored its subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
71
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 93 publications
0
71
0
Order By: Relevance
“…; Plard et al. ). Sex ratios of offspring born on different dates have also proven to be a particularly interesting subject of study.…”
Section: Introductionmentioning
confidence: 97%
“…; Plard et al. ). Sex ratios of offspring born on different dates have also proven to be a particularly interesting subject of study.…”
Section: Introductionmentioning
confidence: 97%
“…It can be strongly affected by demographic structure generating individual heterogeneity in the vital rates of individuals (Vindenes et al ). Some important sources of individual heterogeneity include spatial heterogeneity (Beckage and Clark , Reid et al ), genetic variation (Postma and van Noordwijk , Coulson et al ) and lasting effects of early life conditions (Beckerman et al , Plard et al ). Earlier studies have shown that the demographic variance can be positively or negatively affected by individual heterogeneity (demographic structure), as compared to a model where the structure is ignored (Vindenes et al , Vindenes and Langangen 2015).…”
mentioning
confidence: 99%
“…For instance, we have previously shown that earlier birth dates can result in larger size at maturation in N. ocellatus (Pen et al., ). This pattern of early birth date conferring an advantage later in life is observed across vertebrates, with evidence in some species of mammals and many bird species (e.g., Arnold, Hatch, & Nisbet, ; Green & Rothstein, ; Plard et al., ; Saino et al., ). While growth rates were affected by birth date, we found no effect on offspring survival over the first winter.…”
Section: Discussionmentioning
confidence: 79%